(untitled) (Journal of Engineering Science, 2020)
The high-strength mild steel bars (usually low carbon steel) are widely used for structural purposes throughout the world including Bangladesh. The strength of these deformed barsis measured through a sample decimation process via Universal Testing Machine (UTM), after which the broken pieces are discarded as scrap for recycling. Therefore, measuring the hardness of steel could be a good indication of strength and will involve less sample and short time for testing. The strength–hardness relationship for steel and cast iron is well defined. However, the TMT 500W deformed bar using in Bangladesh has different structural phenomena due to its unique fabrication technique. Therefore, it is necessary to understand how the strength varies with hardness for this grade of steel. The current research aims to explore the hardness–strength relationship for TMT (Thermomechanical Treatment) 500W bar as an alternate of the tensile test to minimize the wastage, cost and time of testing. Several TMT 500W bars were collected from the local market and measured the Rockwell Hardness B (HRB), strength and other relevant macroscopic/microscopic parameters. Finally, two empirical relationships of yield and tensile strength have been established using rim hardness, core hardness, and rim thickness data. The actual strength data shows a good agreement with present findings and the result variation is found less than 2% and 3% in the case of yield strength and tensile strength respectively. Journal of Engineering Science 11(1), 2020, 113-122